The True secret of writing: Connecting life with language - Matalie Goldberg (Atria Paperback, 2014)
These are the barest bones of Natalie Goldberg's revolutionary writing and life practice, which she details in The True Secret of Writing, her first book on the silent intensives she has taught for over a decade in small groups in Taos, New Mexico. This is a whole new slant on writing since her perennial bestseller, Writing Down the Bones-and it's now available to everyone. With luminous reflections on the rich life of the mind and heart that writing awakens, Goldberg guides readers through their own personal or group retreat, illuminating the steps of sitting in silent open mind, walking anchored to the earth, and writing without criticism. Just as Goldberg cuts through her students' resistance with her no-nonsense instructions-"Shut up and write"-The True Secret of Writing cuts to the core of self-understanding and connecting with the world. The capstone to four decades of teaching, The True Secret of Writing is Goldberg's Zen boot camp, her legacy teaching. Its stories of her own students' breakthroughs and insights give moving testament to how brilliantly her unique, tough-love method works.